From Truth Commission to Truth Project: the evolution of Mississippi’s incomplete Truth Commission, 2005–2010 - Whitlinger, Claire (International journal of transitional justice, 2022)
Just months after the Mississippi Truth Commission’s public launch in 2009, organizers abandoned the Commission despite sufficient funding and growing public support, deciding instead to pursue a statewide oral history project. This study explores why, offering insight into an understudied phenomenon: incomplete truth commissions. Drawing on ethnographic observations, archival documents and interviews with local practitioners, this study highlights several reasons that local organizers changed course. In addition to a shifting cultural context, the Mississippi Truth Commission faced several cognitive challenges. First, local audiences struggled to comprehend the structure and scope of the truth commission model, leading to ‘Transitional Justice 101,’ a perpetual, and ultimately unsuccessful, public education program. Second, local organizers’ visit to South Africa in 2009 cast doubt on the efficacy of truth commissions and caused them to question the metaphoric logic that had constructed Mississippi’s history of racial violence as analogous to South Africa’s, providing implicit justification for the Commission until that point. Thus, alongside economic and political resources, this research suggests that cognitive resources are a critical, and often overlooked, component of truth commissions’ infrastructure. Findings also indicate that incomplete truth commissions can be leveraged to support alternative truth-seeking processes that may be more advantageous in stable democracies.